2015
DOI: 10.1186/s13027-015-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CK19 expression, deregulation of normal keratinocyte differentiation pattern and high risk-human papilloma virus infection in oral and oropharyngeal squamous cell carcinoma

Abstract: BackgroundSimple epithelial keratins appear early during embryonic development and are expressed in non-stratified, ductal and pseudo-stratified epithelial tissues. CK19, the lowest molecular weight keratin, is also expressed in basal layer of squamous epithelia of mucosal surfaces. Previous studies have shown that High Risk-Human Papilloma Virus (HR-HPV) epithelial infection induces cell immortalization via E6 and E7 viral proteins and this, in turn, impairs cytokeratin expression in cancerous cells lines der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…In the past, a relationship between HPV and basaloid morphology of head and neck squamous cell carcinoma has been suggested [18,19], but it is now accepted that not all BSCC cases are associated with HPV, and HPV status is more closely related to the location than histology of SCC [20,21]. A recent study suggested a relationship between high-risk HPV and CK19 expression [22], but two of three HPV-positive cases in this study were negative for CK19.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a relationship between HPV and basaloid morphology of head and neck squamous cell carcinoma has been suggested [18,19], but it is now accepted that not all BSCC cases are associated with HPV, and HPV status is more closely related to the location than histology of SCC [20,21]. A recent study suggested a relationship between high-risk HPV and CK19 expression [22], but two of three HPV-positive cases in this study were negative for CK19.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of studies have reported a close link between CK7 or CK19 and HPV positive OPSCC, little is known about the roles played by CK7 and CK19 in the pathogenesis of HPV‐related SCC . However, a few studies have analyzed interactions between HPV16 E7 mRNA and CK7 and CK19 in cervical cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of studies have reported a close link between CK7 or CK19 and HPV positive OPSCC, little is known about the roles played by CK7 and CK19 in the pathogenesis of HPV-related SCC. 7,8,10 However, a few studies have analyzed interactions between HPV16 E7 mRNA and CK7 and CK19 in cervical cancer cell lines. [11][12][13] In particular, in SiHa cells containing CK7/CK19, CK19 promotes HPV16 E7 oncoprotein expression by binding to the 6-mer peptide SEQIKA of CK7, which interacts with E7 mRNA and inhibits E7 mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations